Modeling Diffusion in Functional Materials: From Density Functional Theory to Artificial Intelligence. (23rd July 2019) - Elbaz, Yuval; Furman, David; Caspary Toroker, Maytal
Abstract: Diffusion describes the stochastic motion of particles and is often a key factor in determining the functionality of materials. Modeling diffusion of atoms can be very challenging for heterogeneous systems with high energy barriers. In this report, popular computational methodologies are covered to study diffusion mechanisms that are widely used in the community and both their strengths and weaknesses are presented. In static approaches, such as electronic structure theory, diffusion mechanisms are usually analyzed within the nudged elastic band (NEB) framework on the ground electronic surface usually obtained from a density functional theory (DFT) calculation. Another common approach to study diffusion mechanisms is based on molecular dynamics (MD) where the equations of motion are solved for every time step for all the atoms in the system. Unfortunately, both the static and dynamic approaches have inherent limitations that restrict the classes of diffusive systems that can be efficiently treated. Such limitations could be remedied by exploiting recent advances in artificial intelligence and machine learning techniques. Here, the most promising approaches in this emerging field for modeling diffusion are reported. It is believed that these knowledge‐intensive methods have a bright future ahead for the study of diffusion mechanisms in advanced functional materials. Abstract : Modeling diffusion processes is a significant aspect of developing functional materials, e.g. ion conductors for energy applications. Commonly, modeling diffusion is done by computational science methodologies such as density functional theory and molecular dynamics. Modern approaches are taking advantage of artificial intelligence methods to accelerate research and to find heuristic models.